2021
DOI: 10.1590/1413-785220212902242330
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Covid-19 on Brazilian Orthopedists

Abstract: Objective: The aim of this study is to assess the economic impact of the new coronavirus (COVID-19) on Brazilian Orthopaedic Surgeons. Methods: The questionnaire was applied to orthopedists and it questions how long they have worked in this area; their monthly financial impact during the pandemic; what sector was impacted the most; if they had or didn’t have any financial reserves and how long they would last; if they had any other source of fixed income; and how much time off they had taken from work. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…This number is relatively low, given reports across the world, which shows that the average response rate to questionnaires sent by e-mail is 48%. 10 However, among similar Brazilian and international studies performed on hand surgeons and those with other specialties that sent out questionnaires during the pandemic in 2020, Gomes et al 4 obtained a response rate of 18%, Stirma et al 11 had a response rate of 5.7%, and Qazi et al 12 obtained a response rate of 15%. Our sample of 25% was representative of the total regional distribution of specialists in our population; 55.2% were in the southeast, 16.7% were in the south, 13.3% were in the northeast, 8.6% were in the central west, and 7.6% were in the north.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This number is relatively low, given reports across the world, which shows that the average response rate to questionnaires sent by e-mail is 48%. 10 However, among similar Brazilian and international studies performed on hand surgeons and those with other specialties that sent out questionnaires during the pandemic in 2020, Gomes et al 4 obtained a response rate of 18%, Stirma et al 11 had a response rate of 5.7%, and Qazi et al 12 obtained a response rate of 15%. Our sample of 25% was representative of the total regional distribution of specialists in our population; 55.2% were in the southeast, 16.7% were in the south, 13.3% were in the northeast, 8.6% were in the central west, and 7.6% were in the north.…”
Section: Discussionmentioning
confidence: 98%
“…13 In surgical specialties, it was necessary to cancel elective procedures and outpatient consultations due to the high risk of exposure of people to the virus and with the intention of minimizing the use of essential items and supplies needed for the postoperative care of COVID patients, such as beds, personal protective equipment, and ventilators. 11 In March 2020, Ducournau et al 14 sent an online questionnaire to 47 hand surgeons from 34 different countries. The results demonstrated that 82% of specialists changed their usual work practice; 60% performed only emergency surgeries, 58% changed their surgical indications and indicated more conservative treatments, and 90% changed their office practice by deselecting patients and using telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic surgeons’ incomes changed during COVID-19 pandemic [ 10 , 14 , 15 ]. The rapidly spreading threat imposed an unprecedented burden on the effectiveness and sustainability of the healthcare systems.…”
Section: Orthopedic Practice In Covid-19 Pandemicmentioning
confidence: 99%
“…According to a survey of 975 orthopaedic surgeons in Brazil, approximately 98% of them suffered some monetary impact; 80% had a financial reserve from which 45% could last for three months. Longer the time of professional experience, greater the reduction percentage of the monthly income [ 14 ].…”
Section: Orthopedic Practice In Covid-19 Pandemicmentioning
confidence: 99%
“…To the Editor, we would like to share ideas on the publication “Economic impact of COVID-19 on Brazilian orthopedists.” 1 Stirma et al concluded that “There was a direct relationship between the professional experience in this subspecialty and a higher percentage of fixed income, as well as a greater impact on the reduction percentage in the monthly budget and a longer time off the job.” 1 The pandemic affected many people worldwide, including medical personnel. People working at a private establishment were probably affected by the lockdown.…”
mentioning
confidence: 99%